Emerging Role of High-Mobility Group Box 1 (HMGB1) in Liver Diseases - Ruochan Chen; Wen Hou; Qiuhong Zhang; Rui Kang; Xue-Gong Fan; Daolin Tang (BMC, 2013)
Abstract Damage-associated molecular pattern (DAMP) molecules are essential for the initiation of innate inflammatory responses to infection and injury. The prototypic DAMP molecule, high-mobility group box 1 (HMGB1), is an abundant architectural chromosomal protein that has location-specific biological functions: within the nucleus as a DNA chaperone, within the cytosol to sustain autophagy and outside the cell as a DAMP molecule. Recent research indicates that aberrant activation of HMGB1 signaling can promote the onset of inflammatory and autoimmune diseases, raising interest in the development of therapeutic strategies to control their function. The importance of HMGB1 activation in various forms of liver disease in relation to liver damage, steatosis, inflammation, fibrosis, tumorigenesis and regeneration is discussed in this review.